Online Learning Quality Control in the Pandemic Covid-19 Era in Indonesia - Giatman, Muhammad; Siswati, Sri; Basri, Irma Yulia (Journal of Nonformal Education, 2020)
The Covid-19 pandemic that hit the world in early 2020, has rapidly changed the structure of people's lives, including Indonesia. The world of education is forced to replace face-to-face learning with online learning. The Rector of UNP has followed up on the central government policy to shift the face-to-face (conventional) learning process into online learning. For this reason, the UNP Quality Assurance Center needs to ensure that the implementation of online learning has gone well and is able to meet the predetermined learning-outcame (LO). Through the distribution of learning assessment instruments circulated using google-form to 40,000 UNP students, it was found that 4820 respondents had filled in the instrument. From the respondents' answers, it is known that 99.3% of the lecturers have conducted online lectures, 58% of them are according to the schedule. From the aspect of student readiness, 43.9% were ready, 40.5% were not ready. Furthermore, 50.2% of the lecturers provided guidance well, 44.4% sometimes, and only 5.4% did not. The main obstacles for students: 39.8% less stable internet and 47.7% signal difficulties and no signal at all 12.4%. Other difficulties are 82% internet access, 75.9% credit fees, 63.7% tuition fees, and 51.6% other difficulties. E-learaning process at UNP has been going well and can meet the learning outcomes that have been set. To improve the quality of better learning outcomes, it is necessary to improve the quality of network infrastructure by Telkom, increase the quality of instructional learning by lecturers, and provide credit subsidies for students.